AGENT-BASED PRODUCTION MANAGEMENT SYSTEM FOR TFT-LCD FAB - Shin, Moonsoo; Ryu, Taebeum; Ryu, Kwangyeol (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
Thin film transistor-liquidcrystal display (TFT-LCD) fabs are highly capital-intensive. Therefore,to ensure that a fab remains globally competitive, production must take placeat full capacity with high utilization of resources and must employjust-in-time principles that require on-time delivery with minimum work-in-process (WIP).However, limited space and lack of material handling capacity act asconstraints that hamper on-time delivery to process equipment.Therefore, to build an efficient production management system, a material handling model should beincorporated in the system. In this paper, anagent-based production management system is proposed for a TFT-LCD fab. Every manufacturing resource (including process equipment and material handling equipment), as well as WIP, isrepresented as anindividual agent. The agent simulates operational behavior ofassociated equipment or WIP. This paper also proposes a simulation model by usingan event graph-based approach.